2006
DOI: 10.1074/jbc.m510382200
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Endonuclease G in Nucleosomal DNA Fragmentation under Sustained Endogenous Oxidative Stress

Abstract: We have previously shown that inhibition of catalase and glutathione peroxidase activities by 3-amino-1,2,4-triazole (ATZ) and mercaptosuccinic acid (MS), respectively, in rat primary hepatocytes caused sustained endogenous oxidative stress and apoptotic cell death without caspase-3 activation. In this study, we investigated the mechanism of this apoptotic cell death in terms of nucleosomal DNA fragmentation. Treatment with ATZ؉MS time-dependently increased the number of deoxynucleotidyl transferase-mediated n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 71 publications
2
60
1
Order By: Relevance
“…13,35 Experiments using antioxidants further indicate that ROS acts upstream of Bax relocation and mitochondrial depolarization. 13 We observed that NAC substantially inhibited ROS production, upregulation of p53, conformational changes of Bax, disruption of the DC m , and cell death induction.…”
Section: Discussionmentioning
confidence: 99%
“…13,35 Experiments using antioxidants further indicate that ROS acts upstream of Bax relocation and mitochondrial depolarization. 13 We observed that NAC substantially inhibited ROS production, upregulation of p53, conformational changes of Bax, disruption of the DC m , and cell death induction.…”
Section: Discussionmentioning
confidence: 99%
“…EndoG knock-out mice have no defect in apoptotic DNA degradation (16,17), but this might be due to redundancy with CAD and additional nucleases (1,2,18). RNA interference experiments and genetic data in Saccharomyces cerevisiae support a role of EndoG in apoptosis (8,19,20). EndoG is also thought to function in a non-apoptotic form of programmed cell death (21).…”
mentioning
confidence: 95%
“…Endo G is a mitochondrial nuclease that has been suggested to play a role in mitochondrial DNA replication (38), and its role in nuclear DNA fragmentation during apoptosis has been evidenced from the studies on Caenorhabditis elegans (39,40). The release of Endo G from mitochondria and its translocation to nuclei have been documented in different cell lines during apoptotic stimuli (41)(42)(43). In Leishmania, both Cyt c and Endo G have been reported to play important roles in apoptosis (6).…”
Section: Tm Promotes Cyt C and Endo G Release From Mitochondria And Smentioning
confidence: 99%